FEATURES OF MOTOR SKILLS EDUCATION USING MOBILE GAMES FOR CHILDREN FROM PRIMARY SCHOOL - Mocrousov Elena (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
In the article submitted for publication is reflected the experimental material for the implementation of socially important problems such as the educational process in primary schools in the Republic of Moldova, which is to apply new approaches and technologies in interdependence with the physical education and upbringing. The school age is especially favorable to train and increase the necessary complex movements for children. Moreover, in the primary school, is the most easy to assimilate and improve the various forms of motor actions, that is explained, above all, by the intensive development of the functions of the motor analyzer. Therefore, the physical education of pupils in secondary schools, especially in the early grades, it is necessary to focus on creating the proper organization for necessary conditions.